Respuesta :

9514 1404 393

Answer:

     y: 0, 6, 12, 18, 24

Step-by-step explanation:

Put the value of x in the equation and do the arithmetic.

For x = -1,

  y = 6(-1) +6

  y = -6 +6 = 0

For x = 0,

  y = 6(0) +6

  y = 0 +6 = 6

If you're paying attention, you can see that increasing x by 1 will make the value of y go up by 6. We can see the values of x increase by 1 from each to the next. This means the y numbers on the bottom row increase by 6 from each to the next:

  x: -1, 0, 1, 2, 3

  y: 0, 6, 12, 18, 24